OIL QUALITY OF CANOLA CULTIVARS IN RESPONSE TO WATER STRESS AND SUPER ABSORBENT POLYMER APPLICATION QUALIDADE DE ÓLEO DE CULTIVARES DE CANOLA EM RESPOSTA AO ESTRESSE HÍDRICO E APLICAÇÃO DE POLÍMERO HIDROABSORVENTE - Hossein Zahedi; Hamid Reza Tohidi Moghadam; Farshad Ghooshchi (Pesquisa Agropecuária Tropical, 2011)
Water stress significantly limits plant growth and crop yield. Hence, the efficient management of soil moisture and the study of metabolic changes which occur in response to drought stress are important for agriculture. The present study was conducted to evaluate the effect of six oilseed rape (Brassica napus L.) genotypes (Rgs003, Sarigol, Option500, Hyola401, Hyola330, and Hyola420), with and without drought stress, and with and without the use of super absorbent polymer, on oil quality and content. A complete randomized blocks design, with a split-plot arrangement, in a 2x2x6 factorial scheme (drought stress x polymer x genotypes), with three replications, was used. The research was carried out in a farm owned by the Seed and Plant Improvement Institute, in Karaj, Iran. Results showed a significant difference for drought stress levels, presence of super absorbent and genotypes on oil content and composition, as well as on glucosinolate content in the oil. Drought stress conditions decreased the oil and linoleic acid contents, but increased the glucosinolate and stearic acid contents. The use of super absorbent polymer increased the linoleic acid content, but decreased other components. It was possible to conclude that, under drought stress conditions, the super absorbent polymer application, for reserving higher amounts of water in itself, increased the soil ability to store water, what increased the plant vegetative period and consequently the oil quality by decreasing saturate fatty acids and increasing unsaturated fatty acids. O estresse hídrico limita significativamente o crescimento de plantas e a produtividade da cultura. Por isto, o manejo eficiente da umidade no solo e o estudo de alterações metabólicas que ocorrem em decorrência do estresse hídrico são importantes para a agricultura. O presente estudo objetivou avaliar o efeito de seis genótipos de canola (Rgs003, Sarigol, Option500, Hyola401, Hyola330 e Hyola420), cultivados com e sem estresse hídrico e com e sem a presença de polímero hidroabsorvente, na qualidade e teor do óleo extraído de suas sementes. Utilizou-se delineamento em blocos casualizados, com parcelas subdivididas, em esquema fatorial 2x2x6 (estresse hídrico x polímero x genótipos), com três repetições. A pesquisa foi desenvolvida em área pertencente ao Seed and Plant Improvement Institute, em Karaj, Irã. Observou-se efeito significativo para os níveis de estresse hídrico, presença de polímero e genótipos, no teor e composição do óleo e no teor de glucosinolato. O estresse hídrico reduziu os teores de óleo e ácido linoleico, mas aumentou o teor de glucosinolato e de ácido esteárico. A aplicação do polímero hidroabsorvente aumentou o teor de ácido linoleico, mas diminuiu outros componentes. Foi possível concluir que, sob estresse hídrico, a aplicação de polímero hidroabsorvente, em razão de sua maior retenção de água, aumentou a capacidade de armazenamento desta no solo, o que contribuiu para um aumento no período vegetativo da planta, favorecendo a qualidade do óleo, por diminuir o teor de ácidos graxos saturados e aumentar o de insaturados.